Available Courses
Study Groups
Login / Join
Maths Discussion Group
Jeremy Lai Hong
(University of the Witwatersrand, Johannesburg, Gauteng, South Africa)
Can someone explain when to use the product rule?
ALL ANSWERS
Lindani
(, )
lets say f(x)=(x^2) and g(x)=six(x), meaning that, f(x)g(x) = (x^2)sin(x).
then, (f(x)*g(x))' = f'(x)g(x) + f(x)g'(x). think of it as "derive f, keep g, then keep f, derive g"
hence "derive f keep g" is f'(x)g(x) = 2xsin(x) and "keep f derive g" is (x^2)cos(x)
finaly, we have (f(x)g(x))' = 2xsin(x) + (x^2)cos(x)